Lymnaea Rubiginosa as a Host Found in the Babura River, Medan City - Masdiana Sinambela; Andreas Simorangkir; Tonggo Sinaga (Green Publisher Indonesia, 2024)
Lymnaea rubiginosa as a snail host found in the Babura River, Medan City, is a type of snail that is known to be an intermediate host in the life cycle of several trematode worms. Lymnaea rubiginosa was collected using net sources at four research stations and there were 10 sub stations at each research station. Research in 2023 found Lymneae rubiginosa in juvenile form and only at station two was it found, and even then only in one collection and only one individual. Snails can be infected by Fasciola gigantica and by other trematodes such as Echinostoma sp. and Trichobilharzia sp. as well as oligochaete worms, namely Chaetogaster sp. Chaetogaster sp. infection in Lymnaea rubiginosa snails originating from rice fields and ponds shows that the spread of these worms is widespread. If it is suspected that the worm is capable of preying on the Fasciola gigantica miracidium, then Chaetogaster sp. more effective for use as a biological control. If the Lymnaea rubiginosa snail has been infected with E. hystricosum, then the snail cannot be infected again with other trematodes such as Trichobilharzia brevis. There seems to be a mechanism that inhibits the occurrence of mixed infections. Trematode and oligochaete worm infections in the snail's body can affect the development and growth of the snail. There is no mixed infection between two types of trematodes, namely Echinostoma sp. and Streigidae in a snail Lymnaea rubiginosa supports the phenomenon of antagonism.